2020
DOI: 10.1155/2020/7138513
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Its Predictors among Diabetes Mellitus Patients Attending Treatment in Hawassa University Comprehensive Specialized Hospital, Southern Ethiopia

Abstract: Background. Patients with diabetes mellitus are at twice the risk of developing depression than the general population. The coexistence of diabetes and depression largely contributes to increased morbidity and mortality and results in high healthcare cost. Objective. The aim is to assess severity of depression and its determinants in diabetes outpatients at Hawassa University Comprehensive Specialized Referral Hospital, southern Ethiopia. Methods. An institutional-based cross-sectional study was done using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Various studies have documented that factors associated with depression among diabetes patients using the classical logistic regression. Risk factors were age [ 10 , 15 , 34 ], gender [ 14 , 15 , 35 38 ], marital status [ 15 , 35 , 37 , 39 ], educational status [ 34 , 37 , 40 ], hazardous drinking [ 38 , 39 ], medication adherence [ 13 , 39 ], duration lived with DM [ 9 , 14 , 35 ], fasting blood sugar [ 41 ], DM complication [ 10 , 12 , 14 , 36 , 37 ], chronic illness other than DM [ 14 , 34 ], and types of medication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have documented that factors associated with depression among diabetes patients using the classical logistic regression. Risk factors were age [ 10 , 15 , 34 ], gender [ 14 , 15 , 35 38 ], marital status [ 15 , 35 , 37 , 39 ], educational status [ 34 , 37 , 40 ], hazardous drinking [ 38 , 39 ], medication adherence [ 13 , 39 ], duration lived with DM [ 9 , 14 , 35 ], fasting blood sugar [ 41 ], DM complication [ 10 , 12 , 14 , 36 , 37 ], chronic illness other than DM [ 14 , 34 ], and types of medication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of depression in people with diabetes mellitus is about two to three times higher compared to the general population [11][12][13]. Studies have reported varying results on the prevalence of depression in diabetes patients that ranges from 5.9% to 87% [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The 11 articles were published up to August 2021 and involved a total of 3156 participants. Two studies were conducted in the United States [25,26], 2 in Saudi Arabia [27,28], 6 in Africa (5 in Ethiopia and 1 in Nigeria) [29][30][31][32][33][34], and 1 in Thailand [35]. All included studies were cross-sectional.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All included studies were cross-sectional. Among the included studies, 9 were conducted in a hospitalbased setting [26][27][28][29][30][31][32][33]35] and 2 were in a community-based setting [25]. The sample size of the studies ranged from 200 to 403.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation